Organization of personal activity in a society globalized - Ortiz Cabanillas, Pedro (2017)
The study develops an explanation of how a person’s activity is organized, in other words, its performance. For this purpose, it will be defined the structure of the nervous system, and explain the differences among anxiety, attention, and expectation, also it will be defined the three ways of organization of epiconscious activity, knew as the organization that allows a person to anticipate to his/her real, concrete and specific social context, in an immediate or mediate way. It will be presented that exists a coherent theoretical framework with the purpose of keeping a scientific explanation of the human being, that allows, on one side, to affirm that the human neocórtex transforms in the conscious of a person (along the life socially integrated), on the other side, to affirm that the mentioned conscious reflects the society’s structure. From this perspective, this society is not an abstract story, but a material reality that occurs artificially since 30 thousand years, at least. In the last 5 centuries, this reality lives in a system where predominates the global market that has put the economic power above all humanity values.